Recurrent Ileocolic Intussusception in Children: A Scoping Review - Salvatore Arena; Fabiola Cassaro; Giulia Maisano; Pietro Impellizzeri; Carmelo Romeo (International Journal of Pediatrics)
Conclusions: The presence of a PLP does not seem to be associated with the recurrence of intussusception. More than 85% of RI underwent successful nonsurgical management. RI should be safely approached in the same way as primary intussusception, and surgery should be reserved to cases where a PLP has been suspected. In cases of multiple episodes, surgery can be considered an effective way to avoid recurrences, and this possibility should be discussed with parents.